(NsPRAWO^NIK LI^NYH IMEN NARODOW rsfsr (B/s - (NsUPERANSKAQ(B, (Na(B. (Nw(B.,s ((NmOSKWA (B:s (NrUSSKIJ QZYK(B,s, 1987)
(NpREDLAGAEMYJ SLOWARX(B-(NSPRAWO^NIK SODERVIT (B36 (NSPISKOW NAIBOLEE UPOTREBITELXNYH IMEN NARODOW rsfsrs
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmOWOZNAWSTWOs